The market liquidity of interest rate swaps - Ismael Alexander Boudiaf; Immo Frieden; Martin Scheicher (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2024)
This paper studies market liquidity in interest rate swaps (IRS) before and during the global tightening of monetary policy. IRS constitute the single largest derivatives segment globally. Banks and Pension Funds extensively rely on IRS to hedge interest rate risk. Hence, providing an understanding of this market and the drivers of market liquidity is a key research question in the current market context. We use price and volume data from around 338.000 trades in the most active long-horizon swap contract denominated in EUR to construct seven liquidity measures. Taking a comprehensive approach, we apply linear regressions to determine the drivers of variation in liquidity. Our liquidity measures are significantly related to monetary policy, market-wide fixed income liquidity, EURIBOR rate volatility and Dealer behaviour. Indicators for generic market stress such as VIX which are often documented in the literature are not strongly connected to IRS trading conditions.
Keywords: G12; G15; 330; Fixed income; market structure; liquidity; swaps